Olfactory Dysfunction as a Biomarker for Early Diagnosis of Cognitive Impairment in Patients With Type 2 Diabetes: A Systematic Review - Ramos-Cazorla, Paula; Carazo Barrios, Lina; Reyes-Bueno, Jose A.; Sagües-Sesé, Elena; De-Rojas-Leal, Carmen; Barbancho, Miguel A.; Garzón-Maldonado, Francisco J.; de la Cruz-Cosme, C.; García-Arnés, Juan A.; García-Casares, Natalia (Wiley, 2024)
Background: Olfactory dysfunction and cognitive impairment (CI) have been associated with Type 2 diabetes (T2DM), but the mechanisms underlying this association are broadly unknown. This systematic review tends to investigate the relationship between the onset of olfactory dysfunction and CI in patients with T2DM and to explore the potential role of olfactory dysfunction as an early diagnosis biomarker of CI. Methods: We conducted a systematic review consulting PubMed and Scopus. The articles considered eligible included patients with T2DM and cognitive and olfactory test. Results: The search identified a total of 145 articles, of which 13 were finally selected. The majority of these studies discovered a correlation between olfactory dysfunction and CI in individuals with T2DM. Additionally, other biomarkers such as functional magnetic resonance imaging demonstrated changes in brain regions associated with the sense of smell in T2DM patients. Conclusions: Olfactory dysfunction could be a biomarker for early diagnosis of CI in T2DM. However, these alterations are highly heterogeneous and more studies that include neuroimaging need to be conducted.
Keywords: Diabetes tipo 2 - Síntomas; Memoria - Trastornos; Olfato - Trastornos; Anosmia; Diabetes; Mild cognitive impairment; Olfactory dysfunction; Type 2 diabetes